2023
DOI: 10.1186/s12876-023-02800-9
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative serum interleukin-6 levels correlate with survival in stage I-III colorectal cancer

Abstract: Aims The preoperative serum levels of inflammatory mediators, including C-reactive protein (CRP), procalcitonin (PCT) and interleukin-6 (IL-6), have been demonstrated to be correlated with patient outcomes in colorectal cancer (CRC); however, the prognostic role of these levels has been less well-studied in postoperative settings. Materials and methods A total of 122 stage I-III CRC patients were retrospectively enrolled. Serum levels of CRP, PCT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 76 publications
0
6
1
Order By: Relevance
“…After postoperative tumor resection, plasma IL-6 was still induced prominently in the IgG2b, κ group. Escalation of circulating IL-6 levels has been previously reported to associate with systemic inflammation in cancer patients undergoing surgery 52 , thus facilitating EMT and BCSCs expansion 33 and contributing to progressive metastasis 53 . This was matched with increased distant metastasis after scramble and shMCT-1 groups underwent tumor resection (Figure 4 C).…”
Section: Resultsmentioning
confidence: 99%
“…After postoperative tumor resection, plasma IL-6 was still induced prominently in the IgG2b, κ group. Escalation of circulating IL-6 levels has been previously reported to associate with systemic inflammation in cancer patients undergoing surgery 52 , thus facilitating EMT and BCSCs expansion 33 and contributing to progressive metastasis 53 . This was matched with increased distant metastasis after scramble and shMCT-1 groups underwent tumor resection (Figure 4 C).…”
Section: Resultsmentioning
confidence: 99%
“…4,29 However, opposite results were reported for colorectal and breast cancers in early stages. 14,15 IL-6 immunoreactivity has been investigated in the cytoplasm of tumor cells in a large group of CRC patients (n = 160). 10 The IL-6-positive (IL-6 + ) tumor group has been associated with advanced tumor stage, lymph node metastasis, and vascular invasion and do not correlate with serum IL-6 levels.…”
mentioning
confidence: 99%
“…It is a pleiotropic cytokine with distinguished protumor functions stimulating tumor cell proliferation, angiogenesis, metastasis, and tumor progression 11–13 . However, several studies have reported the associations of IL-6 with good prognosis of cancers with different histologic origin 14,15 . Similarly, the higher mRNA expression of IL-6 in malignant melanoma has been reported to associate with longer survival of the patients in comparison with lower mRNA levels, while no such associations have been observed for head and neck squamous cell carcinoma (HNSCC), ovarian and breast cancers 16 …”
mentioning
confidence: 99%
See 2 more Smart Citations